The Role of the General Election Supervisory Body (Bawaslu) In Handling Election Crime Violations in the 2020 Regional Head Election - Boyke, Dwi Intan Anidah; Marsaoly, Muhammad Fazry (International Journal of Education, Information Technology, and Others, 2024)
This research aims to find out what forms of violations were found by the Bawaslu of Tidore Islands City in the 2020 Mayor and Deputy Mayor elections as well as the procedures carried out on these findings/reports of alleged violations by relying on Law No. 10 of 2016 concerning the Second Amendment Based on Law Number 1 of 2015, as well as the role of Bawaslu in handling alleged criminal violations based on General Election Supervisory Agency (Perbawaslu) Regulation Number 8 of 2020 concerning Handling Election Violations for Governors and Deputy Governors, Regents and Deputy Regents, and Mayors and Deputy Mayors City. The research method used is a qualitative research method with an empirical juridical research type or an empirical-sociological legal research type and the approach used in the research is a socio-legal approach (sosio legal approach). The results of the research show that the forms of violations handled during the Election of Mayor and Deputy Mayor in the City of Tidore Islands in 2020 were the handling of violations of the Code of Ethics in 2 cases, election crimes in 12 cases, and other legal acts in 15 cases. For the 12 criminal cases, only 3 (three) cases reached the Tidore District Prosecutor's Office and only 1 case received a permanent court decision. Bawaslu has a role in the process of the initial stages of suspected election crimes from the first, second process, up to the discussion stage together with elements of other institutions, namely the police and prosecutor's office. In the process of reviewing alleged election criminal violations, Bawaslu has a time limit that must be followed in accordance with statutory regulations.